4 - The Role of Historical Societies in Nigeria’s Development - Yakubu A. Ochefu; Chris B.N. Ogbogbo (Afrika Zamani, 2022)
This article examines the contributions of historical societies to the development of their communities. Using the Nigerian example, it posits that a distin- guishing feature of historical societies is in their quest to promote a sense of history among members of a given group or society. This salient feature of such organizations enables them to play a significant role in the task of national development. It proceeds to demonstrate that in promoting historical aware- ness, the role of such societies is inextricably tied to the role of history as a discipline in national development. Having demonstrated the role of historical societies to national development, the article concludes that since development is a product of change, and the subject matter of history focuses on continuity and change, it follows that development can only be understood and appreciated within the context of history. It is this strategic role of history in faciltating development that makes historical societies incubators of development.